Case Report: Niraparib as Maintenance Therapy in A Patient With Ovarian Carcinosarcoma - Zhang, Jie Qing; Zhao, Bing Bing; Wang, Mao Mao; Li, Li (Frontiers in Oncology, 2021)
Ovarian carcinosarcoma (OCS) is a rare, highly aggressive and rapidly progressing malignant tumor with an extremely poor prognosis. So far, due to the low incidence of OCS, there are no large-scale prospective studies exploring the standard care of OCS patients. There is no uniform and effective treatment for OCS. Within the development of precision medicine, targeted therapies (such as PARP inhibitors) have been widely used in epithelial ovarian cancer and various other solid tumors. Here, we report a BRCAwt patient with advanced OCS who experienced a second and a third cytoreductive surgery in June 2017 and October 2019 and has been on niraparib maintenance therapy for more than 20 months after receiving second-line and third-line chemotherapy.